Pd Immobilized in Mesoporous Silica Particles as Recyclable Catalysts for Suzuki–Miyaura Coupling: Cooperative Effects Exerted by Co-Immobilized Amine Functionalities - Dickschat, Arne T.; Surmiak, Sabrina; Studer, Armido (Synlett, 2013)
A bifunctional heterogeneous palladium catalyst bearing additional basic sites was successfully prepared by sequential Cu-catalyzed 1,3-dipolar alkyne–azide cycloaddition and thermal nitroxide-exchange reaction of surface-bound alkoxyamines. This catalyst shows high activity in the Suzuki–Miyaura cross-coupling. The additional basic functionality acts cooperatively since an analogous heterogeneous Pd catalyst lacking the amine functionality is less active. Such catalysts can be recycled up to ten times without loss of activity.
Keywords: mesoporous silica nanoparticles; cooperative Pd catalysis; Suzuki coupling; catalyst immobilization